Population fecundity and reproductive capacity of some food fishes in relation to year-class-strength fluctuations - Serebryakov, V. P. (ICES Journal of Marine Science, 1990)
Population fecundity (PF). i.e. the total number of eggs spawned by a population during the spawning season of a given year, is the fundamental criterion of the reproductive capacity of the population. PF is defined and calculated as a sum of the eggs spawned annually by fish of all age groups composing the spawning section of a population. PF was estimated for Norwegian spring-spawning herring. Barents Sea capelin, and Northeast Arctic cod. Values of PF varied over ranges × 5 in capelin. × 10 in cod. and × 100 in herring. The ratio of the number of fish which survive to age 3 to the total number of eggs spawned in a given year is taken to be an integrated indicator of survival conditions during these first three years of life, and defined as the survival factor (S). The highest S fluctuations of above two orders of magnitude were recorded in herring, whereas in cod and capelin the ranges were 1.5 and 1 order of magnitude, respectively. Average values of S were estimated as 15.9. and 147 fish of age 3 per million eggs in herring, cod. and capelin, respectively. Historical assessment of PF, year-class strength, and S enables the following three levels of reproductive capacity to be identified: (1) safe level, guaranteeing the production of a strong year class under average survival condition during early life; (2) minimal required, implying year-class-abundance fluctuations around the long-term mean; and (3) critical level of population fecundity, posing a real danger of a long-term decline in abundance. These three levels of reproductive capacity are recommended for use as a reference framework when formulating regulatory measures designed to ensure the continuity of an adequate spawning stock.